87Sr/86Sr in Archeological and Paleobiological Research: A Perspective - Sillen, Andrew (Frontiers in Ecology and Evolution, 2021)
The stable isotope ratio 87Sr/86Sr has been shown to have extraordinary potential for documenting the movement and life-histories of humans and other animals, both in history and prehistory. Thirty years of expanding applications has taken the method from a niche (if not fringe) approach to a normal part of archeological and paleobiological enquiry; indeed a “Golden Age.” The technique is inherently interdisciplinary, because in addition to those archeologists and paleobiologists wishing to apply it, most applications require informed input from ecologists, geochemists, and calcified tissue biologists. This perspective explores how such interdisciplinarity is both a strength and an impediment to further advancement.